The Effect of Competence and Work Motivation on Employee Employee Performance with Job Satisfaction as a Mediating Variable at PT Media Musik Pro-active - Nindia Wulandari; Suharto; Harry Indratjahyo (Journal of Islamic Studies & Social Science, 2024)
Indonesia's music industry is rapidly growing, with various genres and artists attracting musicians from various groups and organizations. The development of this industry has made it a highly sought-after and valuable sector for both musicians and the music industry. Major Labels are companies that manage and promote their music, promoting and preserving the rights of their artists. The success of a company can be attributed to the quality of its employees, which can be influenced by various factors such as education, skills, competencies, work ethics, motivation, health, work environment, social issues, work environment, climate change, technology, production, management, and performance. Competencies are essential for individuals to perform their jobs effectively and improve professional quality in their field. Quantitative research methods, such as data collection, analysis, and interpretation, are used to study populations and gather data. The analysis of job performance variables reveals that most employees at PT Media Music Proaktif believe that the indicators of job performance are based on job quality, quantity, performance, and performance. The most significant contribution to job performance is the importance of understanding and implementing these variables for individual and team performance, building relationships between employees and management, and creating a healthy work environment. The most significant contribution to job performance is the quality of work facilities, which can lead to job satisfaction and satisfaction, as demonstrated in the case of AC in the same area.